Redesign Music Photographer Vest: Camera Equipment Organization Solutions for High Mobility - Ahmad Riyadi Swandhani; Bintang Nugraha; Syaridza Mubarak (Fakultas Bahasa dan Seni Universitas Negeri Medan, 2026)
The recent surge in the number of music festivals in Indonesia has presented both opportunities and challenges for photographers documenting pivotal moments at these events. A diverse array of photographic tools, including cameras, lenses, spare batteries, and other accessories, often pose constraints in mobilizing and organizing equipment amidst crowds. This research endeavors to design a vest that enhances the work efficiency and mobility of photographers within a dynamic music festival environment. Employing a qualitative approach, this study utilizes data collection methods such as observations, interviews, questionnaires, and documentation within the active photography community. The design process employs the SCAMPER method, encompassing Substitute, Combine, Adapt, Modify, Put to Another Use, Eliminate, and Reverse, to ensure the resulting vest aligns with the photographers’ needs. The findings indicate that vests with specialized compartment designs facilitate the organization of camera equipment, simplify access during work, and safeguard equipment from damage during crowd mobilization. This product is anticipated to serve as a practical solution that enhances the comfort and safety of photographers at music festivals. Furthermore, this research can serve as a reference for the development of analogous products in the future. The redesign was conceived as a critical response to the inadequacy of the previous design in meeting the evolving demands of users.